2001
DOI: 10.1159/000053843
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Accompanied by Differentiation of Cord Blood-Derived CD34+ Cells to Eosinophils

Abstract: To clarify the relation between the expression of genes such as eosinophil-specific granular proteins and cytokine receptors and the pathogenesis of allergic disease, cord blood-derived CD34+ cells were cultured and differentiated into eosinophils. Gene expression in the cells during the differentiation was determined by real-time reverse transcription PCR (ABI PRISM 7700). CD34+ mononuclear cells cultured with stem cell factor, granulocyte-macrophage colony-stimulating factor (GM-CSF), IL-3, and IL-5 in Iscov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Indeed, it has been reported by others 34 and by us 28 that the level of MBP transcripts in CB-derived developing eosinophils decreases after complete maturation. We also used Genechip to measure the transcripts of major granule proteins in eosinophils derived from 6 patients with atopic dermatitis.…”
Section: Abundant Expression Of Mbp Transcripts In Mcs But Not In Eosmentioning
confidence: 61%
See 2 more Smart Citations
“…Indeed, it has been reported by others 34 and by us 28 that the level of MBP transcripts in CB-derived developing eosinophils decreases after complete maturation. We also used Genechip to measure the transcripts of major granule proteins in eosinophils derived from 6 patients with atopic dermatitis.…”
Section: Abundant Expression Of Mbp Transcripts In Mcs But Not In Eosmentioning
confidence: 61%
“…Because immature CB-derived eosinophils express MBP mRNA but lose it after maturation, 28,34 PB eosinophils seem to be mature enough to produce more MBP. A similar dissociation between protein and mRNA after maturation is also found for histidine decarboxylase 38 and chymase 26 in human MCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have used similar ex vivo differentiation protocols for eosinophil differentiation from CD34 ϩ progenitor cells derived from cord blood or peripheral blood. [46][47][48] Recently, Hashida et al 49 demonstrated that 80% of the cord blood-derived CD34 ϩ cells in their study developed into mature eosinophils after 17 days of differentiation. However, they only distinguished between blast cells and mature eosinophils without mentioning the other stages of eosinophil differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Crooks et al, 1998). Recently, it has been reported that cysteinyl leukotriene receptor is involved in differentiation of HSCs into eosinophils (Hashida et al, 2001). In addition, several eicosanoids have been reported to be involved in stem cell differentiation or proliferation (Desplat et al, 2000;Braccioni et al, 2002).…”
Section: Introductionmentioning
confidence: 99%